2013
DOI: 10.1007/s00580-013-1740-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum biochemical assessment of hepatic and renal functions of rats during oral exposure to glyphosate with zinc

Abstract: A subchronic toxicity study was carried out to assess hepatic and renal functions of rats during oral exposure to glyphosate with zinc for the period of 8 weeks. Forty-eight Wistar rats used for the study were randomized into six groups of eight Wistar rats each, and each group had equal number of male and female Wistar rats. The Wistar rats administered with distilled water at 2 ml/kg body weight served as the control group (DW); others were administered with zinc at 50 mg/kg body weight (Z) group, glyphosate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…As shown, glyphosate use was not likely to induce negative effect on the blood chemistry panel. It was consistent with the previous studies of human occupational exposure 29 30 , but out of accord with the animal studies 47 48 49 50 . It might be attributed to that the relative level of glyphosate intake of the occupational exposed humans was less than that of the oral-administrated experimental animals, and far from enough to induce human health damage.…”
Section: Discussionsupporting
confidence: 92%
“…As shown, glyphosate use was not likely to induce negative effect on the blood chemistry panel. It was consistent with the previous studies of human occupational exposure 29 30 , but out of accord with the animal studies 47 48 49 50 . It might be attributed to that the relative level of glyphosate intake of the occupational exposed humans was less than that of the oral-administrated experimental animals, and far from enough to induce human health damage.…”
Section: Discussionsupporting
confidence: 92%
“…Following Gly administration, it is possible to observe clusters of hepatocytes synthesizing MT, thus demonstrating that Gly induces a cellular response, which includes the nonenzymatic antioxidants pathway. These data are in agreement with those observed in rats, where the histopathological changes engendered by the herbicide ameliorated when the glyphosate exposure was preceded by a zinc supplementation, which was able to induce a massive MT synthesis [49].…”
Section: Discussionsupporting
confidence: 91%
“…Metabolic studies suggested that the concentration of glyphosate and its metabolic products in kidney and liver tissues were 10‐100‐fold (or even greater) higher than that in most other tissues (BfR, ). Acute administration of a commercial product of glyphosate at high doses or subchronic oral exposure for 8 weeks caused renal toxicity in rats (Tizhe et al, ). A long‐term and low‐dose administration regimen (for approximately 2 years) induced gene expression changes in liver and kidney, and the affected genes were related to inflammatory responses and oxidative stress (Mesnage et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are some epidemiological studies suggesting a potential relationship between glyphosate‐based herbicides (together with other factors) and chronic kidney disease of unknown etiology (CKDu) (Jayasumana, Gunatilake, & Senanayake, ; Jayasumana et al, ; Peraza et al, ). Several studies using models of acute or subchronic exposure as well as long‐term exposure have indicated that the kidney may be one of the main targets of glyphosate, and the renal proximal tubule may be a main target site for glyphosate‐based herbicides (Dedeke, Owagboriaye, Ademolu, Olujimi, & Aladesida, ; Hamdaoui et al, ; Mesnage et al, ; Tizhe et al, ; Wunnapuk et al, ). However, some studies have suggested that the formulation of herbicides is more toxic than glyphosate alone (Dedeke et al, ; Gasnier et al, ).…”
Section: Introductionmentioning
confidence: 99%